1997
DOI: 10.1046/j.1365-2699.1997.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and biology of nomadic birds in the Karoo, South Africa

Abstract: Dryland nomadic bird species, as a proportion of all bird species in a biome in southern Africa, are highest in the arid grassland and arid and semi‐arid Karoo in South Africa. Nomadic birds, of which the most widespread species is the greybacked finchlark Eremopterix verticalis (Smith), are most frequently observed in the north‐central and north western Nama Karoo. The species richness of nomadic species is inversely correlated with species richness of all bird species in the Karoo. Since the distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 11 publications
1
59
0
Order By: Relevance
“…Nomadism is a special form of dispersal that is characterized by irregular movements of individuals, groups of individuals, or whole populations to different areas from year to year or within a season (Sinclair 1984, Dean 1997). Nomadism develops most commonly when limiting resources fluctuate spatiotemporally and become patchy and unpredictably available across a region (Sinclair 1984, Dean 1997.…”
Section: Discussion Comparisons Of Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nomadism is a special form of dispersal that is characterized by irregular movements of individuals, groups of individuals, or whole populations to different areas from year to year or within a season (Sinclair 1984, Dean 1997). Nomadism develops most commonly when limiting resources fluctuate spatiotemporally and become patchy and unpredictably available across a region (Sinclair 1984, Dean 1997.…”
Section: Discussion Comparisons Of Speciesmentioning
confidence: 99%
“…Nomadism is the irregular or undirected dispersal of individuals following patchy and unpredictably available resources across a landscape (Sinclair 1984, Dean 1997. It is in effect temporal turnover of populations (Allen and Saunders 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus has not only been on changes to biodiversity as a consequence of species entering the country, but also on traits, vectors and pathways that enable species from South Africa to alter biodiversity in other regions van Kleunen & Johnson 2007;). 19711973197519771979198119831985198719891991199319971999 Although biological invasions by animals have perhaps been less extensively investigated (though e.g. Robinson et al 2007;Shelton et al 2008), temporal changes at a number of spatial scales have been explored.…”
Section: Invasionsmentioning
confidence: 99%
“…Nomadism in birds has been relatively little studied, and surprisingly little is known of the ecological correlates of nomadism. Dean (1997) reported that nomadic species of the South African Karoo tended to be granivores, especially feeding on grass seeds, and further noted that nomadic species that feed on grass tended to be small. Davies (1984) found that nomads tend to feed on seeds or nectar, but also stated that some nomads are raptors, tracking rodent outbreaks.…”
Section: Introductionmentioning
confidence: 99%